Black masterbatch and compound containing tubular carbon for high blackness, brown undertone, and matte surface
Patent Information
- Application Number
- CN202480089595.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2026-10-16
Smart Images

Figure CN122935575A_ABST
Abstract
Description
Background Technology
[0001] Polycarbonate (PC), acrylonitrile-butadiene-styrene (ABS), and acrylonitrile-styrene-acrylate (ASA) plastics are the basis for widely used formulations in a variety of applications, including visible parts for automotive and electrical appliances. For desired aesthetics, molded black parts preferably exhibit a "warm" undertone and a smooth, matte surface finish. However, carbon black is typically developed to maximize both blackness and a "cooler" blue undertone. Therefore, carbon black-containing masterbatches that exhibit both good blackness and a brown undertone are desirable. Summary of the Invention
[0002] We have unexpectedly found that the addition of tubular carbon, such as carbon nanotubes, preferably carbon nanostructures (CNS) or CNS-derived substances as described below, increases the brown base color of carbon black-plastic blends.
[0003] In one embodiment, the polymer masterbatch comprises 40-95% by weight of a polymer, 10-60% by weight of carbon black, and 5-40% by weight of tubular carbon. The polymer comprises polycarbonate (PC), polystyrene (PS), styrene-acrylonitrile (SAN) copolymer, acrylonitrile-butadiene-styrene (ABS) copolymer, acrylonitrile-styrene-acrylate (ASA) copolymer, and copolymers and blends of any of these substances, or copolymers and blends with polybutylene terephthalate, polyethylene terephthalate, poly(methyl methacrylate), polyolefin wax, ethylene-vinyl acetate copolymer wax, glyceryl monostearate, pentaerythritol stearate, or ethylene bis-stearamide. The tubular carbon may be selected from multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), and carbon nanostructures (CNS) derived materials. The tubular carbon may be surface-modified.
[0004] Tubular carbon may comprise a material derived from at least one carbon nanostructure (CNS) dispersed in a polymer and selected from: carbon nanostructures, fragments of carbon nanostructures, broken carbon nanotubes, elongated CNS strands, dispersed CNS, and any combination thereof, wherein the carbon nanostructures or fragments of carbon nanostructures comprise a plurality of multi-walled carbon nanotubes crosslinked in a polymeric structure by branching, interlacing, entanglement, and / or sharing a common wall, wherein the broken carbon nanotubes are derived from the carbon nanostructures and are branched and share a common wall with each other, wherein the elongated CNS strands are derived from the carbon nanostructures and comprise CNTs that have been linearly displaced relative to each other, and wherein the dispersed CNS comprises peeled broken CNTs that do not share a common wall with each other.
[0005] The polymer masterbatch may further contain fillers in granular or fibrous form. Fillers may be selected from pyrolytic silica, precipitated silica, semiconductor oxides, nickel-coated graphite, metals, metal alloys, carbon fibers, graphene, graphite, clay, metal carbides, metal nitrides, metal phosphates, metal sulfates, metal carbonates, metal halides, metal hydroxides, glass, and organic fibers.
[0006] The polymer masterbatch may further include additives selected from flame retardants, toughening modifiers, antioxidants, UV stabilizers, heat stabilizers, scratch resistant agents, and processing aids.
[0007] On the other hand, the thermoplastic compound comprises a polymer masterbatch of any embodiment disclosed herein. The thermoplastic compound comprises 0.05-5% by weight of tubular carbon and 0.2-4% by weight of carbon black and has a 20° gloss level that is at least 5% lower than 60% gloss. The tubular carbon may be selected from multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), and carbon nanostructures (CNS) derived materials. The tubular carbon may be surface-modified. Tubular carbon may comprise a material derived from at least one carbon nanostructure (CNS) dispersed in a polymer and selected from: carbon nanostructures, fragments of carbon nanostructures, broken carbon nanotubes, elongated CNS strands, dispersed CNS, and any combination thereof, wherein the carbon nanostructures or fragments of carbon nanostructures comprise a plurality of multi-walled carbon nanotubes crosslinked in a polymeric structure by branching, interlacing, entanglement, and / or sharing a common wall, wherein the broken carbon nanotubes are derived from the carbon nanostructures and are branched and share a common wall with each other, wherein the elongated CNS strands are derived from the carbon nanostructures and comprise CNTs that have been linearly displaced relative to each other, and wherein the dispersed CNS comprises peeled broken CNTs that do not share a common wall with each other.
[0008] Thermoplastic compounding may further include polymers selected from: polycarbonate, polystyrene, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymers, acrylonitrile-styrene-acrylate copolymers, and any copolymers and blends of these substances. Thermoplastic compounding may further include fillers in granular or fibrous form. Fillers may be selected from pyrolytic silica, precipitated silica, semiconductor oxides, nickel-coated graphite, metals, metal alloys, carbon fibers, graphene, graphite, clay, metal carbides, metal nitrides, metal phosphates, metal sulfates, metal carbonates, metal halides, metal hydroxides, glass, and organic fibers.
[0009] Thermoplastic formulations may further include additives selected from flame retardants, toughening modifiers, antioxidants, UV stabilizers, heat stabilizers, scratch inhibitors, and processing aids. Thermoplastic formulations may have a b0 of at least -1.3, for example, from -1.3 to -1.17. Thermoplastic compound can have a gloss level that is more than 5% lower than that measured at 20° than that measured at 60°.
[0010] The above and other features of the invention (including various details of construction and combinations of components, and other advantages) will now be described in more detail with reference to the accompanying drawings and pointed out in the claims. It should be understood that the specific methods and apparatus embodying the invention are shown by way of illustration and not as a limitation thereof. The principles and features of the invention may be employed in various and many embodiments without departing from the scope of the invention. Attached Figure Description
[0011] Figure 1A and 1B This diagram illustrates the differences between the following: Y-shaped MWCNTs that are not in or derived from carbon nanostructures. Figure 1A ) and branched MWCNTs in carbon nanostructures Figure 1B ).
[0012] Figure 2A and 2B These are TEM images showing the characteristics of multi-walled carbon nanotubes found in carbon nanostructures.
[0013] Figure 3A This is an illustrative description of carbon nanostructure flake material after the carbon nanostructures have been separated from the growth substrate;
[0014] Figure 3B These are SEM images of illustrative carbon nanostructures obtained as sheet materials. Detailed Implementation
[0015] The invention will now be described more fully below with reference to the accompanying drawings, in which illustrative embodiments of the invention are shown. However, the invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make this disclosure thorough and complete, and to fully convey the scope of the invention to those skilled in the art.
[0016] In one embodiment, the polymer masterbatch comprises 40-95% by weight of a polymer, 10-60% by weight of carbon black, and 5-40% by weight of tubular carbon, wherein the polymer comprises polycarbonate (PC), polystyrene (PS), styrene-acrylonitrile (SAN) copolymer, acrylonitrile-butadiene-styrene (ABS) copolymer, acrylonitrile-styrene-acrylate (ASA) copolymer, and any copolymers and blends of these substances with each other, or copolymers and blends with low molecular weight polyolefin waxes and their derivatives, polybutylene terephthalate, polyethylene terephthalate, poly(methyl methacrylate), polyolefin waxes, ethylene-vinyl acetate copolymer waxes, glyceryl monostearate, pentaerythritol stearate, ethylene bis-stearamide, or other lower molecular weight resins and waxes known to those skilled in the art.
[0017] The masterbatch may comprise 40-95% thermoplastic polymer, for example, 50-85% by weight, 60-75% by weight, or 70-80% by weight. The thermoplastic polymer may include any thermoplastic polymer known to those skilled in the art, preferably based on PC, PS, SAN, ABS, or ASA, and any blends or copolymers of these. For example, blends of thermoplastic materials (such as PC) with other polyesters (such as polybutylene terephthalate (PBT) or polyethylene terephthalate (PET)), with poly(methyl methacrylate)-(PMMA), and with styrene-acrylonitrile copolymers are suitable for the embodiments provided herein. Polycarbonate-based polymers and blends are available from Covestro under the names Makrolon, Bayblend, Makroblend, and Apec; from Sabic under the names Geloy, Cycoloy, and Xenoy; and from LG Chem under the name Lupoy. Alternatively, or additionally, the thermoplastic polymer may be blended with low molecular weight polyolefin waxes and their derivatives, ethylene-vinyl acetate copolymer waxes, aliphatic carboxylic acid esters such as glyceryl monostearate, pentaerythritol stearate, fatty acid amides such as ethylene bis-stearamide, and other lower molecular weight resins and waxes known to those skilled in the art.
[0018] The tubular carbon is preferably selected from multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), and carbon nanostructures (CNS) derived materials. In specific examples, the tubular carbon is provided at a loading of 0.05-5% by weight in the compounded formulation, for example 0.1-4% by weight, 0.25-3% by weight, 0.5-2% by weight, 0.75-1.5% by weight, 1-3% by weight, or in CB-tubular carbon masterbatch, in the range of 5%-40% by weight, for example 10%-30% by weight or 15%-25% by weight. Carbon nanostructure (CNS) derived materials may comprise, consist of, or consist substantially of at least one carbon nanostructure (CNS) derived material selected from: carbon nanostructures, fragments of carbon nanostructures, broken carbon nanotubes, elongated CNS strands, dispersed CNS, and any combination thereof. Carbon nanostructures or fragments of carbon nanostructures comprise multiple multi-walled carbon nanotubes cross-linked in a polymeric structure by branching, interlacing, entanglement, and / or sharing a common wall. Broken carbon nanotubes are derived from carbon nanostructures and are branched, sharing a common wall. Elongated CNS strands are derived from carbon nanostructures and include CNTs that have been linearly displaced relative to each other. Dispersed CNS comprises exfoliated broken CNTs that do not share a common wall.
[0019] Therefore, tubular carbon can be a carbon nanostructure (CNS, single CNS), a term herein referring to multiple carbon nanotubes (CNTs) cross-linked in a polymeric structure by branching (e.g., in a dendritic manner), interlacing, entanglement, and / or sharing a common wall. Thus, a CNS can be considered to have CNTs (e.g., MWCNTs) as the basic monomeric unit of its polymeric structure. Typically, CNSs are grown on a substrate (e.g., a fibrous material) under CNS growth conditions. In such cases, at least a portion of the CNTs in the CNS can be aligned substantially parallel to each other, much like the parallel CNT alignment seen in conventional carbon nanotube forests. They can be separated from the substrate to form CNS sheets. Operations performed to prepare the compositions described herein can produce CNS fragments, broken CNTs, and / or elongated CNS strands. The fragments of the CNS are derived from the CNS and, like larger CNSs, comprise multiple CNTs cross-linked in a polymeric structure by branching, interlacing, entanglement, and / or sharing a common wall. The fractured CNTs are derived from CNS and are branched, sharing a common wall. Elongated CNS strands are structures derived from CNS (including fragments derived from CNS and fractured CNTs) where the component CNTs have been linearly displaced relative to each other. Preferably, the operations performed to prepare the compositions described herein produce more fully exfoliated, dispersed CNSs, and these can retain the junctions and intersections between the component CNTs generated during CNS production. Alternatively, or additionally, conventional MWCNTs or SWCNTs that are not part of or derived from carbon nanostructures are also employed in various embodiments.
[0020] Highly entangled CNSs are macroscopic in size and can be considered to have carbon nanotubes (CNTs) as the basic monomeric units of their polymeric structures. For many CNTs in a CNS structure, at least a portion of the sidewalls of a CNT are shared with another CNT. While it is generally understood that each carbon nanotube in a CNS is not necessarily branched, cross-linked, or sharing a common wall with other CNTs, at least a portion of the CNTs in a carbon nanostructure can be interwoven with each other and / or with branched, cross-linked, or wall-sharing carbon nanotubes in the remainder of the carbon nanostructure.
[0021] As is known in the art, carbon nanotubes (CNTs or multiple CNTs) are carbonaceous materials that include at least one sp... 2 Hybridized carbon atom sheets, the sp 2Hybridized carbon atom sheets bond together to form a honeycomb lattice, which forms cylindrical or tubular structures. The carbon nanotubes can be single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs). SWCNTs can be considered as sp... similar to fullerenes. 2 - Hybridized carbon allotropes. The structure is a cylindrical tube consisting of a six-membered carbon ring. On the other hand, similar MWCNTs have several tubes in a concentric cylinder. The number of these concentric walls can vary, for example from 2 to 25 or more. Typically, the diameter of MWCNTs can be 10 nm or larger, compared to 0.7–2.0 nm for typical SWNTs.
[0022] In many of the CNS used in this invention, CNT is MWCNT, which has, for example, at least two coaxial carbon nanotubes. For example, the number of walls present, determined by transmission electron microscopy (TEM) at a magnification sufficient to analyze the wall number in a particular case, can be in the range of approximately 2-30, for example: 4-30; 6-30; 8-30; 10-30; 12-30; 14-30; 16-30; 18-30; 20-30; 22-30; 24-30; 26-30; 28-30; or 2-28; 4-28; 6-28; 8-28; 10- 28; 12-28; 14-28; 16-28; 18-28; 20-28; 22-28; 24-28; 26-28; or 2-26; 4-26; 6-26; 8-26; 10-26; 12-26; 14-26; 16-26; 18-26; 20-26; 22-26; 24-26; or 2-24; 4-24; 6-24; 8-24; 10-24; 12-24; 14-24; 16 -24; 18-24; 20-24; 22-24; or 2-22; 4-22; 6-22; 8-22; 10-22; 12-22; 14-22; 16-22; 18-22; 20-22; or 2-20; 4-20; 6-20; 8-20; 10-20; 12-20; 14-20; 16-20; 18-20; or 2-18; 4-18; 6-18; 8-18; 10-18; 12-1 8; 14-18; 16-18; or 2-16; 4-16; 6-16; 8-16; 10-16; 12-16; 14-16; or 2-14; 4-14; 6-14; 8-14; 10-14; 12-14; or 2-12; 4-12; 6-12; 8-12; 10-12; or 2-10; 4-10; 6-10; 8-10; or 2-8; 4-8; 6-8; or 2-6; 4-6; or 2-4.
[0023] Because CNS is a polymeric, highly branched, and cross-linked network of CNTs, at least some of the chemistry observed in individualized CNTs can also be observed in CNS. Furthermore, several attractive properties often associated with the use of CNTs are also observed in materials containing CNS. These include, to name a few, electrical conductivity, attractive physical properties (including maintaining or achieving good tensile strength when integrated into silicone-based compositions), thermal stability (sometimes comparable to that of diamond crystals or in-plane graphite sheets), and / or chemical stability.
[0024] However, as used herein, the term "CNS" is not a synonym for individualized, unentangled structures such as "monomeric" fullerenes (the term "fullerene" broadly refers to allotropes of carbon in the form of hollow spheres, ellipsoids, tubes (e.g., carbon nanotubes), and other shapes). In fact, many embodiments of the invention highlight the differences and advantages observed or anticipated by using CNSs rather than their CNT building blocks. Without wishing to be bound by a particular interpretation, it is believed that the combination of branching, crosslinking, and wall sharing among carbon nanotubes in CNSs reduces or minimizes van der Waals forces, which are often problematic when individual carbon nanotubes are used in a similar manner, especially when preventing aggregation is desired.
[0025] In addition to performance properties, or as an alternative to performance properties, CNTs that are part of or derived from CNSs may have a number of characteristics, at least some of which can be used to distinguish them from other nanomaterials, such as ordinary CNTs (i.e., CNTs that are not derived from CNSs and can be provided as individualized, original or fresh CNTs).
[0026] In many cases, CNTs present in or derived from CNS have a typical diameter of 100 nanometers (nm) or smaller, for example in the range of about 5 to about 100 nm, such as in the range of about 10 to about 75, about 10 to about 50, about 10 to about 30, about 10 to about 20 nm.
[0027] In a specific embodiment, the length of at least one CNT derived from a CNS is equal to or greater than 2 micrometers, as determined by SEM. For example, the length of at least one CNT derived from a CNS is in the range of 2-2.25 micrometers; 2-2.5 micrometers; 2-2.75 micrometers; 2-3.0 micrometers; 2-3.5 micrometers; 2-4.0 micrometers; or 2.25-2.5 micrometers; from 2.25-2.75 micrometers; from 2.25-3 micrometers; from 2.25-3.5 micrometers; from 2.25-4 micrometers; or 2.5-2.75 micrometers; 2.5-3 micrometers; 2.5-3.5 micrometers; 2.5-4 micrometers; or 3-3.5 micrometers; 3-4 micrometers; or 3.5-4 micrometers or higher. In some implementations, such as those determined by SEM, more than one of the CNTs derived from CNS, for example a portion, such as at least about 0.1%, at least about 1%, at least about 10%, at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, or even more than half, may have a length greater than 2 micrometers, for example, within the ranges described above.
[0028] CNTs found in CNS, fragments of CNS, or fractured CNTs derived from CNS often exhibit a high aspect ratio, with the length typically greater than 100 times the diameter, and in some cases much higher. For example, in CNS (or CNS fragments), the aspect ratio of CNT length to diameter can range from about 200 to about 1000, such as 200-300; 200-400; 200-500; 200-600; 200-700; 200-800; 200-900; or 300-400; 300-500; 300-600; 300-700; 300-800; 300-900; 300-1000; or 400-500. ; 400-600; 400-700; 400-800; 400-900; 400-1000; or 500-600; 500-700; 500-800; 500-900; 500-1000; or 600-700; 600-800; 600-900; 600-1000; 700-800; 700-900; 700-1000; or 800-900; 800-1000; or 900-1000.
[0029] It has been found that in CNS, and in structures derived from CNS (e.g., in fragments of CNS or in broken CNTs or elongated CNS strands or dispersed CNS), at least one CNT is characterized by a certain “branching density.” As used herein, the term “branching” refers to the characteristic in which a single carbon nanotube branches into multiple (two or more) connected multi-walled carbon nanotubes. One embodiment has a branching density according to which at least two branches are present along a two-micrometer length of the carbon nanostructure, as determined by SEM. Three or more branches may also occur.
[0030] Further characterization (e.g., using TEM or SEM detection) can be used to characterize the type of branching found in CNS relative to structures such as Y-shaped CNTs that are not derived from CNS. For example, while Y-shaped CNTs may have catalyst particles at or near branching regions (points), such catalyst particles may not be present at or near branching regions found in CNS, fragments of CNS, broken CNTs, elongated CNS strands, or dispersed CNS.
[0031] Furthermore, or alternatively, the number of walls observed at branched regions (points) in CNS, fragments of CNS, fractured CNTs, or dispersed CNS differs from one side of the branching (e.g., before the branching point) to the other side of the region (e.g., after or past the branching point). For ordinary Y-shaped CNTs (where the same number of walls are observed in both the region before and after the branching point), no such variation in the number of walls is observed, which is referred to herein as “asymmetry” in the number of walls.
[0032] exist Figure 1A and 1B The document provides diagrams illustrating these features. Figure 1A The example shown is a Y-shaped CNT 11 not derived from CNS. The Y-shaped CNT 11 includes catalyst particles 13 at or near the branching point 15. Regions 17 and 19 are located before and after the branching point 15, respectively. In the case of a Y-shaped CNT such as Y-shaped CNT 11, the two regions 17 and 19 are characterized by the same number of walls, i.e., the two walls shown in the figure.
[0033] Conversely, in CNS ( Figure 1BIn this context, the CNT building block 111 branched at branching point 115 does not contain catalyst particles at or near this point, as seen in the catalyst-deficient region 113. Furthermore, the number of walls present in region 117, which is located before or prior to branching point 115 (or on the first side of branching point 115), differs from the number of walls in region 119 (which is located after, after, or on the other side of branching point 115). More specifically, the three-walled feature found in region 117 does not extend to region 119 (in... Figure 1B In the diagram, region 119 has only two walls, which leads to the aforementioned asymmetry.
[0034] These characteristics are Figure 2A and 2B Highlighted in the TEM image.
[0035] In more detail, Figure 2A CNS branching in TEM region 40 indicates the absence of any catalyst particles. Figure 2B In the TEM, the first channel 50 and the second channel 52 point to the asymmetry of the number of characteristic walls in the branched CNS, while arrow 54 points to the area showing shared walls.
[0036] One, more, or all of these properties may be encountered in compositions containing CNS according to the various embodiments provided herein.
[0037] Suitable techniques for preparing CNS are described, for example, in U.S. Patent Application Publication No. 2014 / 0093728A1, published April 3, 2014; U.S. Patent Nos. 8,784,937B2, 9,005,755B2, 9,107,292B2; and 9,447,259B2. The entire contents of these documents are incorporated herein by reference.
[0038] As described in these documents, CNS can be grown on suitable substrates, such as catalytically treated fibrous materials. The product can be a fibrous CNS material. In some cases, the CNS is separated from the substrate to form a sheet.
[0039] As seen in US2014 / 0093728A1, carbon nanostructures obtained as sheet materials (i.e., discrete particles with finite sizes) exist as three-dimensional microstructures due to the entanglement and cross-linking of their highly aligned carbon nanotubes. This aligned morphology reflects the formation of carbon nanotubes on a growth substrate under rapid carbon nanotube growth conditions (e.g., a few micrometers per second, such as about 2 to 10 micrometers per second), thereby inducing substantially perpendicular carbon nanotube growth from the growth substrate. Without being bound by any theory or mechanism, it is believed that the rapid rate of carbon nanotube growth on the growth substrate can at least partially contribute to the complex structural morphology of the carbon nanostructures. Furthermore, the packing density of CNSs can be tuned to some extent by adjusting the carbon nanostructure growth conditions, including, for example, by changing the concentration of transition metal nanoparticle catalyst particles disposed on the growth substrate to initiate carbon nanotube growth.
[0040] The flakes can be further processed, for example by cutting or fluffing (which may involve mechanical ball milling, grinding, blending, etc.), chemical processes, or any combination thereof.
[0041] In some embodiments, the CNS used is “coated,” also referred to herein as “sizing” or “encapsulated” CNS. In a typical sizing process, a coating is applied to the CNTs forming the CNS. The sizing process can form a partial or complete coating that is non-covalently bonded to the CNTs and, in some cases, can act as an adhesive. Alternatively, an adhesive can be applied to the already formed CNS during a post-coating (or encapsulation) process. In the case of an adhesive with adhesive properties, the CNS can be formed, for example, into larger structures, granules, or pellets. In other embodiments, the formation of granules or pellets is independent of the sizing process.
[0042] The amount of coating can vary. For example, relative to the total weight of the coated CNS material, the coating can range from about 0.1% by weight to about 10% by weight (e.g., by weight, in the range of about 0.1% to about 0.5%, about 0.5% to about 1%, about 1% to about 1.5%, about 1.5% to about 2%, about 2% to about 2.5%, about 2.5% to about 3%, about 3% to about 3.5%, about 3.5% to about 4%, about 4% to about 4.5%, about 4.5% to about 5%, about 5% to about 5.5%, about 5.5% to about 6%, about 6% to about 6.5%, about 6.5% to about 7%, about 7% to about 7.5%, about 7.5% to about 8%, about 8% to about 8.5%, about 8.5% to about 9%, about 9% to about 9.5%, or about 9.5% to about 10%).
[0043] Various types of coatings can be selected. In many cases, sizing solutions typically used for coating carbon fibers or glass fibers can also be used for coating CNS. Specific examples of coating materials include, but are not limited to, fluoropolymers such as poly(vinyl difluoroethylene) (PVDF), poly(vinyl difluoroethylene-co-hexafluoropropylene) (PVDF-HFP), poly(tetrafluoroethylene) (PTFE), polyimides, and water-soluble adhesives such as poly(ethylene oxide), polyvinyl alcohol (PVA), cellulose, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone (PVP), and copolymers and mixtures thereof. In many implementations, the CNS used is treated with polyurethane (PU), thermoplastic polyurethane (TPU), or polyethylene glycol (PEG).
[0044] In some cases, polymers such as epoxy, polyester, vinyl ester, polyetherimide, polyetherketoneketone, polyphthalamide, polyetherketone, polyetheretherketone, polyimide, phenol-formaldehyde, bismaleimide, acrylonitrile-butadiene-styrene (ABS), polycarbonate, polyethyleneimine, polyurethane, polyvinyl chloride, polystyrene, polyolefin, polypropylene, polyethylene, polytetrafluoroethylene, elastomers such as polyisoprene, polybutadiene, butyl rubber, nitrile rubber, ethylene-vinyl acetate polymers, siloxane-based polymers (including those described below), and fluorosilicone polymers, combinations thereof, or other polymers or polymer blends may also be used. If desired, conductive polymers such as polyaniline, polypyrrole, and polythiophene may also be used to enhance conductivity.
[0045] The coating material can be selected to impart specific properties to the thermoplastic composition, or because of its dispersibility, compatibility, and / or miscibility with the thermoplastic polymer used to produce it.
[0046] In many implementations, the CNS is separated from its growth substrate and can be provided in the form of loose granular material (e.g., CNS flakes, granules, agglomerates, etc.) or in a composition that also includes a coating or encapsulating agent and / or in granular or agglomerated form. The specific embodiments described herein employ CNS material having a CNT purity of 97% or higher. Alternatively, the CNS material may include a portion of the growth substrate, wherein it is desirable to include glass fibers in the composition.
[0047] In some embodiments, the CNS is provided as a sheet material after being removed from the growth substrate on which the carbon nanostructures were initially formed. As used herein, the term "sheet material" refers to discrete particles having a finite size. For example, Figure 3AThe illustration shown is an illustrative depiction of the CNS flake material after isolation from the growth substrate. The flake structure 100 may have a first dimension 110 with a thickness ranging from about 1 nm to about 35 μm, particularly from about 1 nm to about 500 nm, including any value and any fraction thereof. The flake structure 100 may have a second dimension 120 with a height ranging from about 1 μm to about 750 μm, including any value and any fraction thereof. The flake structure 100 may have a third dimension 130, which may range from about 1 μm to about 750 μm, including any value and any fraction thereof. Two or all of dimensions 110, 120, and 130 may be the same or different.
[0048] For example, in some embodiments, the second dimension 120 and the third dimension 130 may independently be on the order of about 1 micrometer to about 10 micrometers, or about 10 micrometers to about 100 micrometers, or about 100 micrometers to about 250 micrometers, about 250 to about 500 micrometers, or about 500 micrometers to about 750 micrometers.
[0049] The length of CNTs within a CNS can vary from approximately 10 nanometers (nm) to approximately 750 micrometers (μm) or higher. Therefore, CNTs can be 10nm-100nm, 10nm-500nm; 10nm-750nm; 10nm-1 μm; 10nm-1.25 μm; 10nm-1.5 μm; 10nm-1.75 μm; 10nm-2 μm; or 100nm-500nm, 100nm-750nm; 100nm-1 μm; 100-1.25 μm; 100-1.5 μm; 100-1.75 μm; 100-2 μm; 500nm-750nm; 500nm-1 μm; 500nm-1 μm; 500nm- 1.25 μm; 500 nm - 1.5 μm; 500 nm - 1.75 μm; 500 nm - 2 μm; 750 nm - 1 μm; 750 nm - 1.25 μm; 750 nm - 1.5 μm; 750 nm - 1.75 μm; 750 nm - 2 μm; 1 μm - 1.25 μm; 1.0 μm - 1.5 μm; 1 μm - 1.75 μm; 1 μm - 2 μm; or 1.25 μm - 1.5 μm; 1.25 μm - 1.75 μm; 1 μm - 2 μm; or 1.5 - 1.75 μm; 1.5 - 2 μm; or 1.75 - 2 μm. In some embodiments, at least one CNT has a length equal to or greater than 2 μm as determined by SEM.
[0050] Figure 3B The image shows an exemplary carbon nanostructure obtained as a sheet material, with an SEM image. Figure 3BThe carbon nanostructures shown exist as three-dimensional microstructures due to the entanglement and cross-linking of their highly aligned carbon nanotubes. This aligned morphology reflects the formation of carbon nanotubes on the growth substrate under rapid carbon nanotube growth conditions (e.g., a few micrometers per second, such as about 2 to 10 micrometers per second), thereby inducing the growth of carbon nanotubes substantially perpendicular to the growth substrate. Without being bound by any particular theory or mechanism, it is believed that the rapid rate of carbon nanotube growth on the growth substrate can at least partially contribute to the complex structural morphology of the carbon nanostructures. Furthermore, the packing density of the carbon nanostructures can be tuned to some extent by adjusting the carbon nanostructure growth conditions, including, for example, by changing the concentration of transition metal nanoparticle catalyst particles disposed on the growth substrate to initiate carbon nanotube growth.
[0051] Sheet-like structures can comprise a network of carbon nanotubes in the form of carbon nanotube polymers (i.e., "carbon nanopolymers") with molecular weights ranging from approximately 15,000 g / mol to approximately 150,000 g / mol, including all values and any fraction thereof. In some cases, the upper limit of the molecular weight range can be even higher, including approximately 200,000 g / mol, approximately 500,000 g / mol, or approximately 1,000,000 g / mol. Higher molecular weights can be associated with long-sized carbon nanostructures. Molecular weight can also be a function of the diameter of the predominant carbon nanotubes present within the carbon nanostructure and the number of carbon nanotube walls. The crosslinking density of the carbon nanostructure can be approximately 2 mol / cm³. 3 - Approximately 80 mol / cm 3 Within a certain range. Typically, the crosslinking density is a function of the growth density of carbon nanostructures on the surface of the growth substrate, the carbon nanostructure growth conditions, etc. It should be noted that typical CNS structures (comprising many CNTs held in an open network arrangement) eliminate or reduce the effect of van der Waals forces. This structure can be more easily peeled off, making the many additional steps of separating it or decomposing it into branched structures unique and different from ordinary CNTs.
[0052] In a network morphology, carbon nanostructures can exhibit relatively low packing density. The produced carbon nanostructures can have a density of approximately 0.003 g / cm³. 3 - Approximately 0.015 g / cm³ 3 The initial packing density. Further consolidation and / or coating to produce carbon nanostructured sheet materials or similar morphologies can increase the packing density to approximately 0.1 g / cm³. 3 - Approximately 0.15g / cm 3The scope is defined. In some embodiments, optional further modification of the carbon nanostructures can be performed to further alter the packing density and / or other properties of the carbon nanostructures. In some embodiments, the packing density of the carbon nanostructures can be further altered by forming a coating on the carbon nanotubes of the carbon nanostructures and / or wetting the interior of the carbon nanostructures with various materials. Coating the carbon nanotubes and / or wetting the interior of the carbon nanostructures can further tailor the properties of the carbon nanostructures for various applications. Furthermore, forming a coating on the carbon nanotubes can desirablely facilitate the handling of the carbon nanostructures. Further compaction can increase the packing density to about 1 g / cm³. 3 The upper limit, where chemical modification of carbon nanostructures increases the packing density to approximately 1.2 g / cm³. 3 The upper limit.
[0053] In addition to the aforementioned flakes, CNS materials can also be provided as granules, pellets, or other forms of loose granular materials, with typical particle sizes in the range of about 1 mm to about 1 cm, for example, about 0.5 mm to about 1 mm, about 1 mm to about 2 mm, about 2 mm to about 3 mm, about 3 mm to about 4 mm, about 4 mm to about 5 mm, about 5 mm to about 6 mm, about 6 mm to about 7 mm, about 7 mm to about 8 mm, about 8 mm to about 9 mm, or about 9 mm to about 10 mm.
[0054] Commercially, examples of suitable CNS materials are those available from Applied Nanostructured Solutions LLC (ANS) (Massachusetts, USA), a wholly owned subsidiary of Cabot Corporation.
[0055] The CNS used in this article can be identified and / or characterized by various techniques. Electron microscopy (e.g., techniques such as transmission electron microscopy (TEM) and scanning electron microscopy (SEM)) can provide information about characteristics such as the frequency of a specific number of walls present, branching, and the absence of catalyst particles. See, for example... Figure 2A-2B .
[0056] Raman spectroscopy can point to bands associated with impurities. For example, the D band (approximately 1350 cm⁻¹). -1 Related to amorphous carbon; G band (approximately 1580 cm⁻¹) -1 This is associated with crystalline graphite or CNTs. The G' band (approximately 2700 cm⁻¹) is expected to be... -1 It appears at approximately twice the D-band frequency. In some cases, CNS and CNT structures can be distinguished by thermogravimetric analysis (TGA).
[0057] Suitable carbon black particles can have a size of 15-1500 μm.2 / g Brunauer-Emmett-Teller (BET) surface area, for example 15-75m² 2 / g、75-150m 2 / g, 100-300m 2 / g, 200-500m 2 / g, 500-1000m 2 / g, or 1000-1500m 2 / g. Optionally, or additionally, suitable carbon black may have an oil adsorption value (OAN) of 30-350 mL / 100g, for example 40-80 mL / 100g, 60-150 mL / g, 100-200 mL / g, 150-250 mL / g, 200-300 mL / g, or 250-350 mL / g. Preferred carbon black has a primary particle size of up to 40 nm, for example 10 nm-25 nm, for example 15 nm-25 nm.
[0058] Suitable commercially available carbon black granules include: carbon black sold under the trademarks Regal®, BlackPearls®, Spheron®, Sterling®, and Vulcan® from Cabot Corporation; carbon black sold under the trademarks Raven®, Statex®, Furnex®, and Neotex®, as well as the CD and HV series, from Birla Carbon (formerly Columbia Chemicals); carbon black sold under the trademark Ketjenblack from Lion Specialty Chemicals Co., Ltd.; and carbon black sold under the trademarks Corax®, Durax®, Ecorax®, and Purex®, as well as the CK series, from Orion Engineered Carbons (formerly Evonik and Degussa Industries); and carbon black from Denka and Timcal. Alternatively, or additionally, the carbon black may be furnace black, gas black, thermal black, acetylene black, or lampblack. The carbon black may be recycled carbon black recovered from plastic or elastomeric materials.
[0059] Carbon black can be present in any concentration, typically in masterbatches or blended formulations that do not contain tubular carbon. Typical carbon black concentrations in masterbatches can be 10-60% by weight, for example 15-25% by weight or 20-30% by weight. Typical carbon black concentrations in blended formulations can be 0.2-4% by weight, for example 0.5-3.5% by weight, 1-3% by weight, or 1.5-2.5% by weight, but higher concentrations are also suitable.
[0060] As mentioned above, carbon black can also be used in combination with conventional CNTs in fresh or virgin form. These CNTs are not derived from CNS, for example, during processing. Suitable CNTs include multi-walled CNTs (MWCNTs) and single-walled CNTs (SWCNTs). SWCNTs can also provide thermal conductivity.
[0061] Any tubular carbon material used herein may be modified to add hydroxyl, carboxyl, amino, alkyl, halogen, metal atoms, and other groups, including oxidation, linking small molecules via diazo chemical linking, optionally followed by metallization, esterification, amidation, halogenation, adding groups via cycloaddition, alkylation, metallization, and other modifications known to those skilled in the art.
[0062] In many cases, tubular carbon is commercially available, including from ChengDu Organic Chemicals Co., Ltd., Sigma-Aldrich, Nanocs, Inc., Skyspring Nanomaterials, Inc., OCSiAl, Nanocyl SA, Nano-C, Shenzhen Sanshun Nano New Materials Co., Ltd., Cabot Corporation, etc.
[0063] The preferred implementation relies on masterbatch compounding technology to prepare the masterbatch or concentrate, wherein the tubular carbon and carbon black are first dispersed into a thermoplastic matrix that is the same as or compatible with the thermoplastic matrix of the final compound. Pre-dispersing the tubular carbon in the masterbatch allows for the production of the final composition at lower shear rates. Sufficient dispersion of the carbon black, tubular carbon, and other additives in the thermoplastic can be achieved using equipment such as twin-screw or three-screw extruders, internal kneading mixers, continuous mixers, reciprocating co-kneaders, and other mixing equipment known to those skilled in the art, by any method known to them. The masterbatch may include one or more further components or additives, such as flame retardants, toughening modifiers, antioxidants, UV stabilizers, heat stabilizers, scratch resistant agents, processing aids, and / or other additives known to those skilled in the art to be incorporated into the final composition. Optionally, or additionally, the masterbatch may include at least one filler in granular or fibrous form, and is selected from pyrolytic silica, precipitated silica, semiconductor oxides, nickel-coated graphite, metals, metal alloys, carbon fibers, graphene, graphite, clay, metal carbides, metal nitrides, metal phosphates, metal sulfates, metal carbonates, metal halides, metal hydroxides, glass, and organic fibers. In many embodiments, the masterbatch includes lubricants, antioxidants, or both.
[0064] The masterbatch can be combined with another carbon black and tubular carbon-free resin in a suitable ratio to form a compound according to any method known to those skilled in the art. Any equipment known to those skilled in the art, such as the equipment listed above, can be used. The other resin can be any thermoplastic polymer and blend described above for the masterbatch. Suitable addition ratios can range from about 1% by weight to about 90% by weight (based on the addition ratio of the masterbatch to the carbon black and tubular carbon-free resin). Exemplary addition ratios relative to the carbon black and tubular carbon-free resin are 1-70% by weight, for example, 5-50% by weight, 10-30% by weight, 2-7% by weight, or 5-15% by weight. The carbon black-free resin may include one or more additional components or additives, such as the additives and fillers listed above, and other substances known to those skilled in the art, to be incorporated into the final composition. Optionally, or additionally, such additional components, additives, or fillers may be combined with the let-down composition in further processing steps.
[0065] The processing steps performed in the preparation of the masterbatches or blends described herein can produce CNS-derived materials (e.g., CNS fragments, broken CNTs, elongated CNS strands, and / or dispersed CNS) that become individually distributed (e.g., uniformly) throughout the system or the entire precursor used to deliver the CNS. For example, shear forces associated with blending operations used to disperse CNS into the masterbatch can lead to the fragmentation of the initial structure and / or the “peeling” of carbon nanotubes from the original CNS.
[0066] Besides their reduced size, CNS fragments (the term also includes partially fragmented CNS) generally share the properties of intact CNS and can be identified by electron microscopy and other techniques, as described above. For example, under appropriate applied shear, when the crosslinks between CNTs within a CNS break, broken CNTs, elongated CNS strands, and dispersed CNS can be formed.
[0067] Illustrative CNS fragment sizes present in thermoplastic systems (masterbatches or blends) containing CNS can range from about 0.5 to about 20 μm, for example, from about 0.5 to about 1 μm; from about 1 to about 5 μm; from about 5 to about 10 μm; from about 10 to about 15 μm; or from about 15 to about 20 μm. MWCNTs and / or SWCNTs, if used, can range from about 0.1 μm to about 10 μm.
[0068] In many masterbatches and blended compositions, tubular carbon and carbon black are uniformly distributed throughout the polymer matrix.
[0069] It was found that the presence of tubular carbon, such as MWCNTs, SWCNTs, and / or CNS-derived substances, such as CNS, CNS fragments, broken nanotubes, elongated CNS strands, and / or dispersed CNS, in carbon black-filled thermoplastic compositions can exhibit an improved brown tint (less negative b). and / or a that is not too negative And reduced gloss.
[0070] In some embodiments, tubular carbon and carbon black are used in combination with one or more additional additives or fillers (such as those described above and other additives commonly used in thermoplastic compounds). Such additives may be incorporated with tubular carbon and carbon black in the masterbatch and / or added together with other thermoplastic elastomers during the formation of the final compound.
[0071] The compositions described herein can be used to prepare a variety of molded or extruded articles, including but not limited to automotive parts such as grilles, pillars, rearview mirror systems, door handles, dashboard frames, appliance enclosures, and consumer products such as coffee makers, juicers, and hair dryers.
[0072] Compounds produced by combining the masterbatch with other polymers may have a b value of at least -1.3 (less negative than -1.3), for example at least -1.25 or from -1.3 to -1.15 or from -1.27 to -1.17. Value (as L) a b (part of the color). Alternatively, or additionally, the 20° gloss of the blend may be at least 5% less than the 60% gloss, for example, from less than 5% to less than 45%, from less than 10% to less than 25%, or from less than 15% to less than 35%.
[0073] The invention is further illustrated by the following non-limiting embodiments.
[0074] Example
[0075] Test methods
[0076] Color data (L) was generated using a DATACOLOR 850 instrument conforming to the CIELAB colorimetric standard. a b The color measurement scheme used a D65 illuminator, a d / 8° measurement geometry, and a 10° observer. Data was recorded in L-mode including specular reflection (SCI). a b Data. The gloss of the injection-molded panel surface was determined using a BYK-Gardner 4520 Micro-TRI Gloss Meter. Prior to testing, the device was calibrated using a polished black glass plate with an arbitrary value of 100. Gloss measurements were first taken at a 60° angle and then at a 20° angle.
[0077] Preparation of masterbatch
[0078] Carbon black pigment (Black Pearls 800 carbon black, Cabot Corporation) and / or CNS are mixed with base resin (KIBISAN® PN-107 acrylonitrile-styrene copolymer (SAN) (Chimei Corporation) or Makrolon 2207 polycarbonate (Covestro)) using a Farrel 1.57L internal mixer according to the following mixing scheme (Table 1) to prepare a masterbatch (MB) consisting of base resin and pigment in the relative amounts specified in Table 2.
[0079] Table 1. Internal mixer setup for producing masterbatch
[0080]
[0081] Table 2. Masterbatch Compositions
[0082]
[0083] Comparative example
[0084] Masterbatch thinning and injection molding sheet preparation
[0085] First, MB was dry-blended with diluted resin (Makrolon 2805 polycarbonate from Covestro), and then compounded using the parameters in Table 3 on a Leistritz ZSK27 iMAXX co-rotating twin-screw extruder with a screw diameter of 28 mm and an L / D ratio of 48. Plates with injection molding dimensions of 90 mm × 65 mm × 2 mm were used for color and gloss evaluation. The PC compound was first dried at 120°C for 4 hours, and then injection molded using a 36 mm injection molding machine SE100EV-A from Sumitomo Demag using the parameters in Table 4.
[0086] Table 3. Parameter settings for compounding in a twin-screw extruder
[0087]
[0088] Table 4. Injection Molding Parameter Settings for PC and PC / ABS
[0089]
[0090] Table 5 shows the color and gloss data of the polycarbonate blends prepared using CNS and carbon black. The results indicate that increasing the amount of CNS decreases gloss and increases the brownish tint (not too negative b). ), and moderately increased (lower L) Darkness.
[0091] Table 5. Color and surface gloss data of PC blends with different amounts of CB and CNS, injection molded colored samples.
[0092]
[0093] Comparative example
[0094] In a further example, masterbatch 4 was first dry-blended with PC / ABS resin (Bayblend T85XF from Covestro) and then dried at 120°C for 4 hours. Using a 36mm injection molding machine SE100EV-A from Sumitomo Demag, with the parameters in Table 4, 90mm × 65mm × 2mm sheets were directly injection molded for color and gloss evaluation. It is expected that the blend with 0.1 wt% CNS and 0.35 wt% carbon black will have a color comparable to, but with a more brownish hue (less negative b) than a CNS-free composition with the same carbon black loading but lower gloss. and / or a ).
[0095] While the invention has been specifically shown and described with reference to preferred embodiments thereof, those skilled in the art will understand that various changes in form and detail may be made therein without departing from the scope of the invention as covered by the appended claims.
Claims
1. Polymer masterbatch, comprising: 40-95% by weight of a polymer, said polymer comprising polycarbonate, polystyrene, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, and any copolymers and blends of these substances with each other, or copolymers and blends with polybutylene terephthalate, polyethylene terephthalate, poly(methyl methacrylate), polyolefin wax, ethylene-vinyl acetate copolymer wax, glyceryl monostearate, pentaerythritol stearate or ethylene bis-stearamide; 10-60% by weight of carbon black; and 5-40% by weight of tubular carbon.
2. The polymer masterbatch according to claim 1, wherein the tubular carbon is selected from multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), and carbon nanostructures (CNS) derived materials.
3. The polymer masterbatch according to claim 2, wherein the tubular carbon is surface-modified.
4. The polymer masterbatch according to any one of claims 1-3, wherein the tubular carbon comprises a substance dispersed in the polymer and selected from at least one carbon nanostructure (CNS) derived material: carbon nanostructure, fragments of carbon nanostructure, broken carbon nanotubes, elongated CNS strands, dispersed CNS, and any combination thereof. The carbon nanostructures or fragments thereof comprise multiple multi-walled carbon nanotubes, which are cross-linked in the polymeric structure through branching, interlacing, entanglement, and / or sharing a common wall. The fractured carbon nanotubes are derived from the carbon nanostructure and are branched, sharing a common wall. The elongated CNS strands are derived from the carbon nanostructures and include CNTs that have been linearly displaced relative to each other. The dispersed CNS comprises peeled, fractured CNTs that do not share a common wall with each other.
5. The polymer masterbatch according to any one of claims 1-4, further comprising fillers in granular or fibrous form.
6. The polymer masterbatch according to claim 5, wherein the filler is selected from pyrolytic silica, precipitated silica, semiconductor oxides, nickel-coated graphite, metals, metal alloys, carbon fibers, graphene, graphite, clay, metal carbides, metal nitrides, metal phosphates, metal sulfates, metal carbonates, metal halides, metal hydroxides, glass, and organic fibers.
7. The polymer masterbatch according to any one of claims 1-6 further comprises additives selected from flame retardants, toughening modifiers, antioxidants, UV stabilizers, heat stabilizers, scratch resistant agents, and processing aids.
8. A thermoplastic compound comprising the polymer masterbatch of any one of claims 1-7, wherein the thermoplastic compound comprises 0.05-5% by weight of tubular carbon and 0.2-4% by weight of carbon black and has a 20° gloss that is at least 5% less than 60% gloss.
9. The thermoplastic compound of claim 8, wherein the tubular carbon is selected from multi-walled carbon nanotubes (MWCNTs), single-walled carbon nanotubes (SWCNTs), and carbon nanostructures (CNS) derived materials.
10. The thermoplastic compound of claim 9, wherein the tubular carbon is surface-modified.
11. The thermoplastic compound according to any one of claims 8-10, wherein the tubular carbon comprises a substance dispersed in the polymer and selected from at least one carbon nanostructure (CNS) derived material: carbon nanostructure, fragments of carbon nanostructure, broken carbon nanotubes, elongated CNS strands, dispersed CNS, and any combination thereof. The carbon nanostructures or fragments thereof comprise multiple multi-walled carbon nanotubes, which are cross-linked in the polymeric structure through branching, interlacing, entanglement, and / or sharing a common wall. The fractured carbon nanotubes are derived from the carbon nanostructure and are branched, sharing a common wall. The elongated CNS strands are derived from carbon nanostructures and include CNTs that have been linearly displaced relative to each other. The dispersed CNS comprises peeled, fractured CNTs that do not share a common wall with each other.
12. The thermoplastic compound according to any one of claims 8-11, further comprising a polymer selected from polycarbonate, polystyrene, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene-acrylate copolymer, and any copolymers and blends of these substances.
13. The thermoplastic compound according to any one of claims 8-12, further comprising fillers in the form of granules or fibers.
14. The thermoplastic compound according to claim 13, wherein the filler is selected from pyrolytic silica, precipitated silica, semiconductor oxides, nickel-coated graphite, metals, metal alloys, carbon fibers, graphene, graphite, clay, metal carbides, metal nitrides, metal phosphates, metal sulfates, metal carbonates, metal halides, metal hydroxides, glass, and organic fibers.
15. The thermoplastic compound according to any one of claims 8-14, further comprising an additive selected from flame retardants, toughening modifiers, antioxidants, UV stabilizers, heat stabilizers, scratch resistant agents, and processing aids.
16. The thermoplastic compound according to any one of claims 8-15, wherein the thermoplastic compound has a b content of at least -1.3, for example -1.3 to -1.
17. .
17. The thermoplastic compound according to any one of claims 8-16, wherein the thermoplastic compound has a gloss level measured at 20° that is more than 5% lower than the gloss level measured at 60°.
Citation Information
Patent Citations
Carbon nanostructures and methods of making the same
US20140093728A1
Glass substrates having carbon nanotubes grown thereon and methods for production thereof
US8784937B2
CNS-infused carbon nanomaterials and process therefor
US9005755B2
Carbon nanostructure-coated fibers of low areal weight and methods for producing the same
US9107292B2
Composite materials formed by shear mixing of carbon nanostructures and related methods
US9447259B2